2022
DOI: 10.1002/admi.202201214
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Stoichiometric NiFeMo Solid Solutions; Tuning the Hydrogen Adsorption Energy via Molybdenum Incorporation

Abstract: in a slow HER kinetics, while on the upside Ni offers several positive characteristics, such as high conductivity, stability and relatively high earth abundance. [1,3] Since the 1960's there has been a significant effort to improve the catalytic activity of Ni-based electrocatalysts with a large variety of promising candidates such as nickel hydroxides, dichalcogenides, phosphides, carbides, and others. [1,4] Generally, the catalytic activity can be enhanced by increasing the active surface area by tuning the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 61 publications
(48 reference statements)
3
1
0
Order By: Relevance
“…The discrepancy in the optimal Mo concentration obtained in theoretical calculations may be attributed to several factors, including the selection of slab surface, adsorption sites, defects or vacancies in the samples used in experiments, and the associated interaction and charge transfer (due to orbital hybridization). It was already reported that Mo dopants could improve the HER performance up to a certain Mo concentration, , in agreement with our findings. For instance, while the optimum HER activity for NiFeMo was reached at 9 at % Mo content, its enhancement for Ni–Mo–P nanocrystals was observed up to the Mo concentration of 4.2% …”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…The discrepancy in the optimal Mo concentration obtained in theoretical calculations may be attributed to several factors, including the selection of slab surface, adsorption sites, defects or vacancies in the samples used in experiments, and the associated interaction and charge transfer (due to orbital hybridization). It was already reported that Mo dopants could improve the HER performance up to a certain Mo concentration, , in agreement with our findings. For instance, while the optimum HER activity for NiFeMo was reached at 9 at % Mo content, its enhancement for Ni–Mo–P nanocrystals was observed up to the Mo concentration of 4.2% …”
Section: Resultssupporting
confidence: 94%
“…It was already reported that Mo dopants could improve the HER performance up to a certain Mo concentration, , in agreement with our findings. For instance, while the optimum HER activity for NiFeMo was reached at 9 at % Mo content, its enhancement for Ni–Mo–P nanocrystals was observed up to the Mo concentration of 4.2% …”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Alloying Ni with other transition metals such as Fe, Co, and Mo has been a successful strategy to improve its catalytic activity. [5][6][7][8][9][10] Previous studies have shown that nickel-based binary and ternary alloys containing Mo have great potential for the HER in alkaline media, [10][11][12] where among the most active electrocatalysts reported in recent years is tetragonal Ni 4 Mo. 9,11,12 The high activity of Ni 4 Mo has been attributed to its band structure that mimics Pt.…”
Section: Introductionmentioning
confidence: 99%